Effect of Nigella sativa on ischemia-reperfusion induced rat kidney damage - Havakhah, Shahrzad (Iran J Basic Med Sci, 2014)
OBJECTIVE(S): There are a few previously reported studies about the effect of Nigella sativa oil on renal ischemia-reperfusion injury (IRI). The aim of the present study was to test the hypothesis whether pre- or post-treatment with N. sativa hydroalcoholic extract (NSE) would reduce tissue injury and oxidative damages in a clinically relevant rat model of renal IRI. MATERIALS AND METHODS: IRI was induced by clamping of bilateral renal arteries for 40 min fallowed by reperfusion for 180 min. NSE was prepared in a Soxhlet extractor and administrated with doses of 150 mg/kg or 300 mg/kg at 1 hr before ischemia induction (P-150 and 300) or at the beginning of reperfusion phase (T-150 and 300), via jugular catheter intravenously. The kidneys were then removed and subjected to biochemical analysis, comet assay or histopathological examination. RESULTS: The kidneys of untreated IRI rats had a higher histopathological score (P<0.001), while in P-150, as well as T-150 and T-300 groups tubular lesions significantly decreased (P<0.001). Pre- and post-treatment with NSE also resulted in a significant decrease in malondialdehyde (MDA) level (P<0.001) and DNA damage (P<0.001) that were increased by renal I/R injury. NSE treatment also significantly restore (P<0.01) the decrease in renal thiol content caused by IRI. CONCLUSION: The present study shows N. sativa extract has marked protective action against renal IRI, which may be partly due to its antioxidant effects.